Factors That Affect Early Marriage in Adolescents - Rismawati; Irmawati; Haris, Hariyanti (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2021)
Risks that threaten reproductive health in women when deciding to marry at an age that should not include abortion, anemia, sexual violence, and cervical cancer. The purpose of this study is to examine the factors that affect early marriage in adolescents This type of research is a quantitative study where the study uses a research design with an observational analytic approach with the design of the Cross-Sectional Study. The population in this study is teenagers in Bulukumpa subdistrict with a total of 50 people. The sample used in the study was 44 adolescents. There is a relationship between the level of education and the incidence of early marriage, there is a relationship between the level of knowledge and the incidence of early marriage, there is a relationship between economic status and the incidence of early marriage. From the results of the study, it is expected that the need to further increase the desire to dig up information and health education for adolescents about marriage. As well as providing motivation and activities that are useful for the development of adolescents since elementary school, the high percent of democratic parenting with the occurrence of early marriage, there is no relationship between cultural factors and the incidence of early marriage, there is a relationship between peer factors and early marriage.